PETA PEMIKIRAN PENDIDIKAN ISLAM DI INDONESIA: Telaah Dikotomi Pendidikan - Taufik, Taufik (Hunafa: Jurnal Studia Islamika, 2010)
The development of  today’seducation in Indonesia  cannot be separated from the  influence of  the  ideas of western state and  those of the Islamic state. The influence brings about the dichotomy of  Islamic education and general education, and the various ideas on the  purposes of education based on religion, politics, and area. Both the Islamic education  institution and general education institution have their own objective of education. The infect is that there will be some intellectuals having no good morals. To minimize the dichotomy of  education  in Indonesia, there must be restoration  of  Islamic education system and public education.Kata Kunci: pendidikan Islam, pendidikan umum, dikotomi pendidikan